Pengaruh Shalat Dhuha terhadap Kedisiplinan Siswa Kelas VIII MTsN Kota Bogor - Indah, Rossa; Mubarak, Zahid; Hambari (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study aims to determine the level of dhuha prayer of students in class VIII MTsN Bogor City, determine the level of discipline of students in class VIII MTsN Bogor City and analyze the effect of dhuha prayer on the discipline of students in class VIII MTsN Bogor City. The research method used in this research is quantitative research. This study uses a population of all VIII grade students of MTsN Bogor City with a sample size of 167 people taken randomly. The instruments used in the study were questionnaires and documentation. The data analysis technique in this study used simple linear regression test analysis with the help of the SPSS 26 application. The results showed that: First, the implementation of dhuha prayer for students in class VIII MTsN Kota Bogor obtained a value in the "good" category with an average value (mean) of 46.64. Second, the discipline of VIII grade students at MTsN Bogor City obtained a value in the "good" category with an average value (mean) of 40.52. And third, the results of the simple regression test obtained a t value of 7.753> t table 1.654, a Sig value of 0.000 <0.05 and a coefficient of determination of 0.267 so that Ho is rejected and Ha is accepted, which means that there is a significant influence between dhuha prayer on the discipline of class VIII students at MTsN Bogor City by 26.7% while the remaining 73.3% is influenced by other factors.